Phenotypic, Metabolic, and Genetic Diversity of the Indonesian Isolates of Rhizopus oligosporus - CAHYA PRIHATNA; ANTONIUS SUWANTO (Microbiology Indonesia, 2010)
Fifteen Rhizopus oligosporus isolates were isolated from a number of tempeh samples obtained from Mataram, Jember, and Bogor, Indonesia; and subjected for characterization based on phenotypic, metabolic, and genetic fingerprinting through internal transcribed spacer (ITS) regions and amplified fragment length polymorphism (AFLP). Based on the growth on solid medium, they can be divided into three groups. Firstly, isolates that produced thick mycelia, dumpy sporangiophore, and scarce spores in agar culture, the second group is isolates that produced thin mycelia, stretched sporangiophore, with abundant spores in agar culture. The third group that only comprises one isolate, FB-06, is morphologically intermediate of the first and the second groups. These characters correlated with their range of temperature tolerance. The first group is less tolerant to high temperature (45 oC) compared with the second group, and the third group is the most tolerant to temperature up to 45 oC. Metabolic fingerprinting showed a very high polymorphism. In general, the result may explain a correlation in which isolates obtained from the same locations shared similar patterns. There is no correlation found between metabolic fingerprints and their phenotypic fingerprints. Rhizopus oligosporus readily dominated the niche and utilized nearly all carbon sources given demonstrate the versatile nature of this fungus. ITS regions identification revealed single nucleotide polymorphisms in four representative isolates examined, whereas AFLP fingerprinting determined each of representative isolates as individually unique. Furthermore, this AFLP profile seemed to agree with their phenotypic characters..